Mortality among Children of below Five Years of Age in India due to Diarrhoeal Diseases and its impact on GDP - Rohit Singh Tomar; Deepika Singh Tomar (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background/Objectives: India has largest children population, but unfortunately this population has seriousenemies in the form of communicable diseases. Diarrhoeal disease is among the biggest killer of children inIndia. Our objective is to analyze the trend of mortality among Indian children due to diarrhea across threemajor age groups. Further to suggest ways to manage this disease effective by adopting preventive measures.Methods/Statistics: Secondary data is analyzed by using ANOVA, Tukey Post hoc and partial correlation.Results & Findings: There is a significant difference between the mortality due to diarrhoeal diseases ofchildren across Neonatal, Post neonatal and under five years of age in India. Post hoc test suggests thatmortality due to diarrhoeal diseases of children is significant for Post neonatal and neonatal age group. Thereis very strong and negative correlation has been found between Gross Domestic Product (GDP) of India andmortality due to diarrhoeal diseases in children.Applications: Better management practices are suggested to control number of cases of diarrhoeal diseasesbased on children age groups. To fight against Post neonatal and children under five years of age mortalitydue to diarrhoeal diseases, government in India can frame similar but effective policies.